2012
DOI: 10.1016/j.taap.2012.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic lipid profiling of deer mice fed ethanol using 1H and 31P NMR spectroscopy: A dose-dependent subchronic study

Abstract: Chronic alcohol abuse is a 2nd major cause of liver disease resulting in significant morbidity and mortality. Alcoholic liver disease (ALD) is characterized by a wide spectrum of pathologies starting from fat accumulation (steatosis) in early reversible stage to inflammation with or without fibrosis and cirrhosis in later irreversible stages. Previously, we reported significant steatosis in the livers of hepatic alcohol dehydrogenase (ADH)-deficient (ADH−) vs. hepatic ADH-normal (ADH+) deer mice fed 4% ethanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…47,53,54,55,56,57,58,59 As summarized in Table 1, these publications encompass studies in different species, with different alcohol feeding protocols and methods of analysis. A brief summary of each of these reports is provided below, including information on the analytical method, experimental model, main findings and conclusions.…”
Section: The Effect Of Chronic Alcohol Consumption On the Hepatic Lipmentioning
confidence: 99%
See 2 more Smart Citations
“…47,53,54,55,56,57,58,59 As summarized in Table 1, these publications encompass studies in different species, with different alcohol feeding protocols and methods of analysis. A brief summary of each of these reports is provided below, including information on the analytical method, experimental model, main findings and conclusions.…”
Section: The Effect Of Chronic Alcohol Consumption On the Hepatic Lipmentioning
confidence: 99%
“…The authors compiled a metabolomic profile of the liver of alcohol-exposed zebrafish, including lipids, combining data collected using 1 H-NMR spectroscopy and GC-MS. Similar to the limitations experienced by Fernando et al ., 58 the identification of individual lipids by 1 H-NMR spectroscopy was limited and only changes in broad lipid categories were identified. For example, alcohol exposure was associated with increased hepatic phosphatidylcholine levels.…”
Section: The Effect Of Chronic Alcohol Consumption On the Hepatic Lipmentioning
confidence: 99%
See 1 more Smart Citation
“…An impaired β oxidation of fatty acids can result in accumulation of lipids in the hepatocytes as reported in ethanol-fed ADH − deer mice (Bhopale et al, 2006; Fernando et al, 2012). However, over expression of enoyl CoA hydratase as found in the livers of ethanol group could be a biological response to compensate an impaired β oxidation of fatty acids.…”
Section: Discussionmentioning
confidence: 87%
“…Chronic alcohol abuse is also known to impair hepatic alcohol dehydrogenase (ADH), a major enzyme involved in the oxidative metabolism of alcohol (Sharakawi, 1984; Panés et al, 1993; Kaphalia et al, 1996). Published work from our laboratory have shown that chronic ethanol feeding via Lieber–DeCarli liquid diet for 60 days increases hepatic lipids and formation of fatty acid ethyl esters (nonoxidative metabolites of ethanol), and causes notable hepatic injury in ADH − deer mice as compared to normal hepatic ADH (ADH + ) deer mice (Bhopale et al, 2006; Fernando et al, 2012). …”
Section: Introductionmentioning
confidence: 99%